The Impact of Organizational Justice on Organizational Citizenship Behavior Using Organizational Politics as Moderator (A Case of Public Sector Universities in Khyber Pakhtunkhwa) - Muhammad Nawaz Khan; Muhammad Tahir Khan (UW Journal of Management Sciences, 2022)
Purpose: This study was conducted to explore the impact of organizational justice (distributive justice (DSJ), procedural justice (POJ) and interactional justice (INTJ)) on organizational citizenship behavior with moderating effect of organizational politics (ORP) on the relationship between organizational justice (ORJ) and organizational citizenship behavior (ORCB). Design/ Methodology: The data was collected from 200 employees working in different capacities at public sector universities of Khyber Pakhtunkhwa through self-administrated questionnaires using random sampling technique. The statistical tools (i.e. reliability, correlation and regression) were used to test the hypothesis. Findings: The result of the regression analysis showed that ORP has a negative moderating impact on the relationship between ORJ (distributive justice(DSJ), procedural justice (POJ) and interactional justice (INTJ)) and ORCB. This study analyzed that in a political situation only prevailing group can relish the rewards and rest of the employees suffer which causes disassociation and low levels of citizenship behavior. Implications: This research study contributes to the literature of management sciences by identifying and applying theoretical concepts unto a different sample and in organizational settings.